Gold Stamp IDs to SRA IDs convertion of the metagenomes of GEMs - Buck, Moritz (Swedish University of Agricultural Sciences, 2020)
A small simple JSON-file containing the mapping from Gold Stamp IDs from the IMG/JGI database to the SRA IDs useable by fastq-dump to download the corresponding metagenomes from NCBI. The GoldIDs are the ones from the Supplemental Table 1 from Nayfach, S., Roux, S., Seshadri, R. et al. A genomic catalog of Earth’s microbiomes. Nat Biotechnol (2020). https://doi.org/10.1038/s41587-020-0718-6, that have been submited to the Short Read Archive. The code used to generate this mapping is available at https://github.com/moritzbuck/jgi2sra_mapper
Keywords: Microbial ecology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi